New Confucian Political Philosophy - Tu Wei-Ming’s Fiduciary Community - Weber, Ralph (Acta Orientalia Vilnensia, 2004)
This paper engages with the thought of the contemporary New Confucian and Harvard scholar Tu Wei-ming. Its particular focus is on what could be termed “New Confucian Political Philosophy.” Yet, is it appropriate to speak of a specific political philosophy within Confucianism, or, more specifically, within its 20th century successor New Confucianism? Is it fit to use familiar categories of political philosophy such as liberal-communitarian, individual-society, or democratic-authoritarian in order to scrutinise New Confucianism? Taking questions such as these seriously, this paper starts with some important methodological issues and only then turns to Tu Wei-ming’s proposal of a fiduciary community, that is, of a community of trust. Among other issues, the Confucian family, self-cultivation, and the concept of politics as rectification are discussed. At the end, Tu Wei-ming’s ideas of how to make this Confucian sense of politics and of community contribute to contemporary political philosophy are briefly addressed.